A new shallow water species of Artemisina Vosmaer, 1885 (Microcionidae, Demospongiae; Porifera) from Northeastern Brazil - Cavalcanti, Thaynã; Santos, George Garcia; Hajdu, Eduardo; Pinheiro, Ulisses (Zootaxa, 2016)
Artemisina is a microcionid characterized by lacking a distinctive choanosomal skeleton or definite spongin fibres, lacking also echinating spicules, and with a nearly radial ectosomal skeleton (Hooper 2002). The genus currently has 19 valid species, six of which are recorded from the Atlantic Ocean (Van Soest et al. 2016): A. erecta Topsent, 1904, A. incrustans van Soest et al., 2013, A. melana van Soest, 1984, A. melanoides van Soest et al., 2013, A. transiens Topsent, 1890 and A. vulcani Lévi, 1963. The present study describes a new species of Artemisina from Northeastern Brazil. Four specimens of Artemisina brasili sp. nov. were collected by snorkelling at Pernambuco State. All specimens were preserved in 80% ethanol and deposited in the Porifera Collections at the Universidade Federal de Pernambuco (UFPEPOR) and Museu Nacional of Universidade Federal do Rio de Janeiro (MNRJ).